2017
DOI: 10.1016/j.copsyc.2017.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting diversity: cultural variation reveals the constructed nature of emotion perception

Abstract: The extent of cultural variation in emotion perception has long been assumed to be bounded by underlying universality. A growing body of research reveals, however, that evidence of universality in emotion perception is method-bound. Without the assumption of underlying universality, new lines of inquiry become relevant. Accumulating evidence suggests that cultures vary in what cues are relevant to perceptions of emotion. Further, cultural groups vary in their spontaneous inferences; mental state inference does… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…Other sources of context, including relational history, perceiver motivation, and affect should also be examined as important sources of variance in emotion perception across societies. Figure adapted from Gendron (2017) .…”
Section: Epoch 1: Constrained Tests Of the Universality Thesismentioning
confidence: 99%
“…Other sources of context, including relational history, perceiver motivation, and affect should also be examined as important sources of variance in emotion perception across societies. Figure adapted from Gendron (2017) .…”
Section: Epoch 1: Constrained Tests Of the Universality Thesismentioning
confidence: 99%
“…Others have argued that the European horror film is distinct from other types of horror film and has a specific “esthetic” (Allmer et al, 2012). There is a considerable literature on the difference between collectivistic and individualistic cultures with research suggesting that the psychological responses of individuals from each type of cultural background are different (Matsumoto et al, 2008; Alotaibi et al, 2017; Gendron, 2017). In the field of horror film perception, experience, and enjoyment, it could be hypothesized that individuals from collectivistic cultures might respond differently to horror (and victims in horror) than do individuals from individualistic cultures – specifically individuals from collectivistic cultures may express greater fear compared to those from individualistic cultures – and this is an hypothesis that can be easily tested.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Cross-cultural validation of databases of facial expressions is particularly advised for a number of reasons. For instance, research has suggested that both the experience and display of emotion (for reviews, see Immordino-Yang and Yang, 2017 ; Niedenthal et al, 2017 ), as well as emotional recognition (for reviews, see Chen and Jack, 2017 ; Gendron, 2017 ) may vary across cultures. Several studies have shown an advantage in emotion recognition when the targets are members of the in-group (e.g., Yan et al, 2017 ; for a review, see Elfenbein, 2015 ).…”
Section: Introductionmentioning
confidence: 99%